2012
DOI: 10.1016/j.steroids.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Acute sex steroid withdrawal increases cholesterol efflux capacity and HDL-associated clusterin in men

Abstract: Exogenous androgens can lower HDL-cholesterol (HDL-C) concentrations, yet men with low serum testosterone have elevated rates of cardiovascular disease (CVD). HDL function may better predict CVD risk than absolute HDL-C quantity. We evaluated the acute effects of medical castration in men on HDL-C, cholesterol efflux capacity and HDL protein composition. Twenty-one healthy men, ages 18–55, received the GnRH antagonist acyline and one of the following for 28 days: Group 1: placebo, Group 2: transdermal testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
10
3
Order By: Relevance
“…T therapy has been shown to reduce HDL3-C subfraction and LpA-I:A-II particles but not the more anti-atherogenic HDL2-c and LpA-I particles (66). Rubinow et al showed that androgen deprivation increased cholesterol efflux from macrophages and demonstrated that sex steroid manipulation modified the HDL proteome (67). Furthermore, T therapy in older hypogonadal men altered HDL protein and lipid composition but did not significantly change serum HDL-mediated cholesterol efflux (68).…”
Section: Discussionmentioning
confidence: 99%
“…T therapy has been shown to reduce HDL3-C subfraction and LpA-I:A-II particles but not the more anti-atherogenic HDL2-c and LpA-I particles (66). Rubinow et al showed that androgen deprivation increased cholesterol efflux from macrophages and demonstrated that sex steroid manipulation modified the HDL proteome (67). Furthermore, T therapy in older hypogonadal men altered HDL protein and lipid composition but did not significantly change serum HDL-mediated cholesterol efflux (68).…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported that apoJ preserves the anti‐inflammatory, antioxidant, and antiatherogenic properties of HDLs (39, 40). Several studies have found that the content of apoJ in HDLs is decreased in subjects with diabetes, obesity, or metabolic syndrome and in patients with active coronary disease (11, 12, 43). In the latter, the antiapoptotic activity of HDLs is compromised in part by its reduced apoJ content (12).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the concentration of apoJ used in our experiments is within the physiologic range. Several studies report that the concentration of apoJ in blood ranges from 50 to 150 mg/ml (41)(42)(43)(44)(45), and the usual concentration of apoB in normolipemic subjects ranges from 0.8 to 1.0 mg/ml. The ratio of apoJ/apoB in blood is therefore around 1/10.…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroid withdrawal in men was shown to increase HDL-associated levels of clusterin (apoJ) while increasing the capacity of HDL to promote cholesterol effl ux from macrophages ( 78 ). A follow-up study showed that testosterone replacement in hypogonadal men promoted signifi cant and clot propagating/inhibiting proteases, although much more work is needed to understand the precise roles they play.…”
Section: Hdl Functional Diversity Matches Its Proteomic Diversitymentioning
confidence: 99%